Ultraperformance convergence chromatography‐high resolution tandem mass spectrometry for lipid biomarker profiling and identification. (29th September 2016) - Jones, Jace W.; Carter, Claire L.; Li, Fei; Yu, Jianshi; Pierzchalski, Keely; Jackson, Isabel L.; Vujaskovic, Zeljko; Kane, Maureen A.
Abstract: Lipids represent biologically ubiquitous and highly dynamic molecules in terms of abundance and structural diversity. Whereas the potential for lipids to inform on disease/injury is promising, their unique characteristics make detection and identification of lipids from biological samples analytically demanding. We report the use of ultraperformance convergence chromatography (UPC 2 ), a variant of supercritical fluid chromatography, coupled to high‐resolution, data‐independent tandem mass spectrometry for characterization of total lipid extracts from mouse lung tissue. The UPC 2 platform resulted in lipid class separation and when combined with orthogonal column chemistries yielded chromatographic separation of intra‐class species based on acyl chain hydrophobicity. Moreover, the combined approach of using UPC 2 with orthogonal column chemistries, accurate mass measurements, time‐aligned low‐ and high‐collision energy total ion chromatograms, and positive and negative ion mode product ion spectra correlation allowed for confident lipid identification. Of great interest was the identification of differentially expressed ceramides that were elevated 24 h post whole thorax lung irradiation. The identification of lipids that were elevated 24 h post‐irradiation signifies a unique opportunity to investigate early mechanisms of action prior to the onset of clinical symptoms in the whole thorax lung irradiation mouse model.